The 'interrogative gaze': Making video calling and messaging 'accountable' - Harper, Richard; Rintel, Sean; Watson, Rod; O'Hara, Kenton (Pragmatics, 2017)
This paper identifies salient properties of how talk about video communication is organised interactionally, and how this interaction invokes an implied order of behaviour that is treated as ‘typical’ and ‘accountably representative’ of video communication. This invoked order will be called an interrogative gaze. This is an implied orientation to action, one that is used as a jointly managed interpretative schema that allows video communication to be talked about and understood as rationally, purposively and collaboratively undertaken in particular, ‘known in common’ ways. This applies irrespective of whether the actions in question are prospective (are about to happen) or have been undertaken in the past and are being accounted for in the present or are ‘generally the case’ – in current talk. The paper shows how this constitutive device also aids in sense making through such things as topic management in video-mediated interaction, and in elaborating the salience of the relationship between this and the patterned governance of social affairs – viz, mother-daughter, friend-friend – as normatively achieved outcomes. It will be shown how the interrogative gaze is variously appropriate and consequentially invoked not just in terms of what is done in a video call or making such calls accountable, but in helping articulate different orders of connection between persons, and how these orders have implications for sensible and appropriate behaviour in video calling and hence, for the type of persons who are involved. This, in turn, explains how a decision to avoid using video communication is made an accountably reasonable thing to do. The relevance of these findings for the sociology of everyday life and the philosophy of action are explored.